Acoustic analysis of pathologies from infancy to young adulthood - Neustein, Amy; Neustein, Amy; Patil, Hemant A.; Patil, Hemant A. (Speech technology and text mining in medicine and healthcare ;, 2020)
This book provides the reader with empirical findings on innovative signal processing approaches to detecting pathologies in infant cries, by comparing new technological approaches to standard ones. The contributors examine novel approaches to machine adaptation to dysarthric speech.